Cellulose-based novel hybrid polymer electrolytes for green and efficient Na-ion batteries. (20th August 2015) - Colò, Francesca; Bella, Federico; Nair, Jijeesh R.; Destro, Matteo; Gerbaldi, Claudio
Graphical abstract: Highlights: A novel cellulosic polymer electrolyte is proposed for Na-ion batteries. Green functional biopolymer is present both in solid electrolyte and electrode. Optimised electrode/electrolyte interface is obtained. Stable cycling in Na/TiO2 and Na/NaFePO4 cells at 55 °C. A simple, cheap and water-based approach for solid Na-ion polymer cells. Abstract: In the present work, a novel pyranose ring laden polymer electrolyte is proposed for all solid Na-ion secondary cells that can operate at moderate temperatures. The prepared fully solid polymer electrolyte film is based on a classic polyethylene oxide (PEO) backbone, homogeneously blended with sodium carboxymethyl cellulose (Na-CMC) and sodium perchlorate. The favourable use of Na-CMC as electrode binder as well as electrolyte additive is evaluated, which would enhance the pathways for forming an optimised electrode/electrolyte interface. The promising prospects of the newly elaborated hybrid electrolyte are investigated by means of galvanostatic charge/discharge cycling in lab-scale cell with TiO2 -based or NaFePO4 -based working electrodes.